PERAN GURU DALAM PENGEMBANGAN KOGNITIF ANAK - Dodi Harianto (P3M IAI Nusantara Batang Hari, 2015)
Teacher is one of the keys to the success of students, both in the social emotional development, especially in developing child cognition, without the active role of the teacher will be one of the developing child cognition, this will result in patal in children for the future. In order to improve the quality of children's cognitive, teachers strive to develop as much as possible in accordance with the child's cognitive development. But often the practice in the field is not in accordance with the spirit and ideals. There are some children who exhibit aggressive behavior as disruptive friends, grabbing a friend, make noise, roads and fro endlessly, hitting friends and screaming. The action taken by the teacher is giving additional tasks to the children who behave aggressively mentioned, this is done so that they can learn seriously, because such children are generally children who have IQ Superior. This paper will explore the role of teachers in the cognitive development of children.